APLIKASI PENERIMAAN SISWA BARU DI SMK SWASTA TERPADU BABUSSALAM BAKTIYA KAB. ACEH UTARA PROV ACEH BERBASIS WEB DENGAN PHP DAN SQL - Zainuddin Zainuddin; Denny Kurniadi (Universitas Negeri Padang, 2019)
In line with the increasingly rapid technology, not a few Vocational High Schools (SMK) are using technology in the service of students and even parents. In order not to compete with State and Private Vocational Schools especially in the North Aceh District of Aceh Province, the Web-based New Student Admission Application is important to be developed at the Babussalam Baktiya Integrated Private Vocational School in North Aceh District of Aceh Province to facilitate new prospective students in the New Student Admission process (PSB ) One effort to improve the New Student Acceptance process and improve service to prospective students, it requires an application that can carry out the New Student Admissions process which is not limited by place. Keywords: Information Systems, New Students, Based on Web, Web, PHP, SQL.